EFEKTIFITAS TABLET FE DALAM MENINGKATKAN KADAR HEMOGLOBIN IBU HAMIL DI PUSKESMAS BANGUN PURBA - daryanti, daryanti; Andria, Andria; Handayani, Eka Yuli (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2023)
Iron deficiency is a condition of a lack of red blood cells (erythrocytes) in a person's blood. Anemia occurs due to a lack of hemoglobin which also means a lack of oxygen throughout the body. If oxygen is reduced the body will become weak, lethargic and not passionate. Anemia in pregnancy occurs because of an increase in plasma that is greater than the increase in hemoglobin levels. This research method is quantitative analytic with the research design used is pre-experimental with one group pre-test and post-test design. Data collection used a Sphygmomanometer, while data analysis used the T-Dependent test. The sample in this study was 38 pregnant women. The results of the research from data analysis, the difference in average Hb levels before and after being given Fe tablets was 1.5 gr% ± 0.57 gr%. And from the results of statistical tests obtained p = 0.00, which means there is an effect of Fe tablets in increasing hemoglobin levels in pregnant women. The conclusion is that there is a significant effect (p value = 0.00). It is expected that the puskesmas will provide counseling and health education to prevent anemia during pregnancy.